Analysis of Variation Characteristics and Driving Factors of Meteorological Drought in Leizhou Peninsula in Recent 60 Years - YANG Huihui; FENG Dezeng; PENG Ying; ZHENG Jinghua; ZHAO Lingling (Renmin Zhujiang)
Leizhou Peninsula, a main crop producing area in South China, is majorly restricted by drought in terms of economic development because most of the rivers in this region are unbranched and the capacity of engineering regulation and storage is insufficient. In this paper, the standardized precipitation and evapotranspiration index (SPEI) at different time scales was calculated to analyze the variation characteristics of meteorological drought in the Leizhou Peninsula and to explore the influence of precipitation, temperature and teleconnection factors on the drought in the Leizhou Peninsula. The results show that: ①The frequency of annual drought in the Leizhou Peninsula is close to 20%, and the northern part shows a significant trend of wetting, while the southern part shows no significant trend of wetting. The northern part is more extreme drought-prone.②Precipitation and temperature are significantly correlated with SPEI, with a stronger correlation between precipitation and drought.③There is a significant negative correlation between the ocean Nino index (ONI) and the SPEI of the following year, indicating that ENSO is closely related to drought, and there is a difference in the impact on drought when the eastern and central ENSO warm events occur. The research results can provide references for the Leizhou Peninsula Irrigation District project to be implemented soon.